Impact of Implementing CYP2C19 Genotype-Guided Antiplatelet Therapy on P2Y12 Inhibitor Selection and Clinical Outcomes in Acute Coronary Syndrome Patients After Percutaneous Coronary Intervention: A Real-World Study in China - Zhang, Yi; Shi, Xiu-Jin; Peng, Wen-Xing; Han, Jia-Lun; Lin, Bai-Di; Zhang, Ru; Zhang, Yun-Nan; Yan, Jia-Lin; Wei, Juan-Juan; Wang, Yi-Fan; Chen, Su-Wei; Nan, Nan; et al. (Frontiers in Pharmacology, 2021)
Background: CYP2C19 loss-of-function (LOF) alleles reduce the effectiveness of clopidogrel in patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS). However, the clinical impact of implementing CYP2C19 gene-guided pharmacotherapy is unclear, especially among the Chinese population. The purpose of this study was to evaluate P2Y12 receptor inhibitor selection and clinical outcomes upon implementation of CYP2C19 genotype-guided pharmacotherapy in current clinical practice. Methods: This was a single-center observational cohort study. Adult PCI patients who received CYP2C19 genetic testing (*2, *3, *17 alleles) were included. Ticagrelor was recommended for patients with a LOF allele. Factors related to P2Y12 inhibitor selection were determined by logistic regression. The primary endpoint was major cardiac or cerebrovascular adverse events (MACCE) within 12 months. MACCE and clinically significant bleeding events (BARC≥2) in the LOF-clopidogrel group, non-LOF-clopidogrel group, and non-LOF-ticagrelor group were compared with those in the LOF-ticagrelor group. The inverse probability of treatment weighting (IPTW) was adjusted in a Cox regression analysis to eliminate confounding factors. Results: Among 1361 patients, 826 (60.7%) had a LOF allele. Patients with a LOF allele were more likely to be prescribed ticagrelor (multivariate-adjusted OR, 1.349; 95% CI, 1.040 to 1.751; p=0.024). The MACCE rate was higher in the LOF-clopidogrel group than in the LOF-ticagrelor group (7.8% vs. 4.0%; log-rank p=0.029; IPTW-adjusted HR, 2.138; 95% CI, 1.300 to 3.515). Compared with the LOF-ticagrelor group, the non-LOF-clopidogrel group showed no significant difference in MACCE rate (5.8% vs. 4.0%; log-rank p=0.272; IPTW-adjusted HR, 1.531; 95% CI, 0.864 to 2.714). Among the patients treated with ticagrelor, there was no significant difference in the MACCE rate between the LOF group and non-LOF group (4.3% vs. 4.0%; log-rank p=0.846; IPTW-adjusted HR, 1.184; 95% CI, 0.582 to 2.410). There was no significant difference in the incidence of clinically significant bleeding events among the four groups. Conclusions: This study confirms that efficiently returned CYP2C19 genotype results did partially guide cardiologists to prescribe ticagrelor for patients with a LOF allele, and that clopidogrel had a higher risk of MACCE than ticagrelor in these patients, which provides support for the implementation of CYP2C19 gene-guided antiplatelet therapy in clinical practice.